The role of long noncoding RNAs in therapeutic resistance in cervical cancer - Zhou, Meimei; Liu, Linlin; Wang, Jing; Liu, Wanru (Frontiers in Cell and Developmental Biology, 2022)
Cervical cancer is one of the common tumors and often causes cancer-related death in women. Chemotherapy is a common cancer therapy, which displays a pivotal clinical benefit for cancer patients. However, chemoresistance becomes a big obstacle for failure of treatment in cancer patients. Recently, long noncoding RNAs (lncRNAs) have been identified to regulate drug resistance in human cancers, including cervical cancer. In this review, we describe the role of lncRNAs in regulation of chemotherapeutic resistance in cervical cancer. We also discuss the molecular mechanisms of lncRNA-mediated drug resistance in cervical cancer. Moreover, we describe that targeting lncRNAs could reverse drug resistance in cervical cancer. Therefore, lncRNAs could become effective therapeutic targets and chemotherapeutic sensitizers for cervical cancer patients.